PENINGKATAN KESADARAN HUKUM MASYARAKAT TERHADAP TRANSAKSI TANAH YANG AMAN DAN BERKEPASTIAN HUKUM - Andi Candra; Putri Sari Nilam Cayo; Husnaini (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This community service program aimed to enhance public legal awareness regarding safe and legally certain land transactions in Pulau Harapan Village, Banyuasin District. Limited public understanding of lawful land sale procedures, the importance of land certificates, and the registration process for the transfer of land rights remains one of the factors contributing to land disputes. The program was conducted through legal education and counseling, case-based learning, Focus Group Discussions (FGD), land transaction simulations, and evaluation through pre-tests and post-tests. The materials covered land rights and their legal status, lawful land sale procedures, the role of Land Deed Officials (PPAT), the importance of land certificates, and strategies for preventing land disputes. The results demonstrated a significant improvement in participants’ understanding of all measured aspects, particularly regarding lawful land transaction procedures, the importance of legal land documents, and land dispute prevention. In addition to improving legal knowledge, the program also increased public awareness of the importance of conducting land transactions in accordance with applicable laws to obtain legal protection and certainty. This program is expected to reduce the potential for land disputes and support orderly land administration in Pulau Harapan Village, Banyuasin District.